The Effect of Changes in the Performance of the Village Head on the Progress of the Unitary Village Community - Liska Febrianti; Nuri Aslami (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Changes in leadership within a certain period are common in Indonesia, be it state, regional, district and village leaders. A village is led by a village head with the highest position who takes part in changing a village, if the performance of the village head is good it will be good and the village he leads will also develop. This study aims to measure the effect of changes in the performance of the new village head on the progress of the community in the unitary village. The method used in this research is the method of observation, as well as interviews with the community and village heads to find out what policies and performance will be carried out by the new village head. Of course, this is something that is highly expected and desired by the entire unitary village community, with the change of the new village head, of course there must be better performance to lead the unitary village community to progress.